2019
DOI: 10.3389/fpsyt.2019.00193
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Meditation, Yoga, and Mindfulness on Depression, Anxiety, and Stress in Tertiary Education Students: A Meta-Analysis

Abstract: Background: Meditation, yoga, and mindfulness are popular interventions at universities and tertiary education institutes to improve mental health. However, the effects on depression, anxiety, and stress are unclear. This study assessed the effectiveness of meditation, yoga, and mindfulness on symptoms of depression, anxiety, and stress in tertiary education students. Methods: We searched Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, PsycINFO and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
131
2
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(162 citation statements)
references
References 81 publications
12
131
2
17
Order By: Relevance
“…placed in conclusions (Breedvelt et al, 2019). We have identified another RCT on yoga and mindfulness including students diagnosed with depression or anxiety, that reported a moderate effect size (Falsafi, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…placed in conclusions (Breedvelt et al, 2019). We have identified another RCT on yoga and mindfulness including students diagnosed with depression or anxiety, that reported a moderate effect size (Falsafi, 2016).…”
Section: Discussionmentioning
confidence: 89%
“…In sum, compared to the control group and controlling for baseline levels in the outcomes and for multiple comparisons, the SKY group benefited six outcomes (depression, stress, mental health, positive affect, mindfulness, and social connectedness), the EI group benefited one outcome (mindfulness), and the MBSR benefited none. SKY's wide range of results may be explained by its multicomponent and comprehensive curriculum including a number of different factors that prior research suggests can improve mental health and psychological thriving: positive psychology (86), yoga/breathing/meditation (87)(88)(89), and community service (90). Modulation of respiration, in particular, has been linked to improvements in neuro-cognitive function (91,92).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, studies on anxiety in education have shown a negative relationship with respect to academic performance [20], content assimilation [21] and metacognitive processes [22]. In contrast, anxiety, in an academic context, has been positively related to stress [23], frustration [24] and emotional distress [25].…”
Section: Mathematical Anxietymentioning
confidence: 99%